THE ANALYZING OF PERSONAL AND PUBLIC TRANSPORT TRAFFIC FLOWS IN BELGOROD AGGLOMERATION - Kushchenko, Liliya; Кущенко, Сергей; Камбур, Алина; Новиков, Александр (Journal of Applied Engineering Science, 2022)
The transport system is the fundamental factor characterizing the quality of life of a megapolis. The economic component also depends on the development of transport in the urban agglomeration, covering the market of goods and services. The growth of global cargo and passenger flows requires better quality requirements for transport infrastructure, and the efficiency of the development of the transport complex is becoming one of the most important transport tasks. The article discusses the features of the organization of traffic in the urban agglomeration of Belgorod. The analysis of incoming flows into the urban agglomeration is carried out. The sections of the urban agglomeration that are the busiest with passenger transport are presented. The main planning characteristics on the stretches of transport streets of the Belgorod with a high level of loading are indicated. A rational solution is proposed to improve the functioning of public and private transport in the urban agglomeration.
Keywords: agglomeration, traffic flow, public transport, personal transport, congestion